Bio-efficacy of Botanicals and Synthetic Pesticides against Pod Boring Weevil (Apion clavipes) and Pod fly (Melanagromyza obtusa) in Pigeon pea - Patra, Sandip; Firake, D. M.; Thakur, N.S. Azad (Indian Journal of Hill Farming, 2018)
A field experiment was conducted at Entomology Farm, ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya to evaluate some botanicals and new generation pesticides against pod borer complex in pigeon pea. Pigeon pea variety ‘Bahar’ was sown in 4m X 3m plot size at 60cm (R-R) X 30cm (P-P) spacing with three replications. Infestation of A. clavipes and M. obtusa was significantly reduced in plots treated with botanicals and chemical pesticides compared to control. Infestation of A.clavipes and M. obtusa was significantly reduced in fipronil 5SC treated plots compared to other treatments. Among botanicals, karanjin 2EC was found to be the most effective treatment against A. clavipes; while pod fly damage was found minimum in neem oil treated plots. Fipronil 5SC was found to be the best insecticides with lowest grain damage and higher benefit cost ratio. Among botanicals; maximum benefit cost ratio was recorded in neem oil treatment.